Культовые памятники и сакральные объекты бесермян: [монография] / Елена Попова - Попова Елена Васильевна (УИИЯЛ УрО РАН, 2011)
Экземпляры: КО (20171219) / Инвентарный номер: 54372 / Цена: / Сис.шифр: 63.5(2Рос.Удм) / Авт.знак: П 58 / ГРНТИ: 03 / ББК: 63.5(2Рос.Удм)